Comparing different approaches to assess individual chronotypes in epidemiological studies (SEVERUS-Cohort). Issue 1 (2nd January 2020) - Valérie Groß, J; Fritschi, Lin; Hellmich, Martin; Schwert, Inga; Renner, René; Pinger, Andreas; Wild, Ursula; Erren, Thomas C
ABSTRACT: Assessing individual chronotypes can become relevant for epidemiological studies, for instance when investigating the impact of night-shift work on human's health. The objective of this study was to explore and compare three different approaches (Self-rating, Munich Chronotype Questionnaire (MCTQ), Perfect Day (PD)) of assessing the chronotype in a group of 48 police officers. We compared the categorical classification of self-rated chronotypes with Mid Sleep Times (MST) on free days from the MCTQ and MST on PDs. Chronotype categories derived from self-rating were only weakly associated with the MST derived from free days (Spearman's rho = 0.33, p = 0.078) and PDs (rho = 0.26, p = 0.073). We found a positive correlation between the MSTs assessed via MCTQ and PD (Pearson's r = 0.67, p < 0.001). There were differences in the MST on free days and on PDs between individuals who did and did not use an alarm clock. All three approaches to assess chronotype information have to be used with caution. Concerns of selection and misclassification bias are raised when assessing chronotypes through the MST on free days for those who do not use alarm clocks. Further research is needed to develop sound strategies to assess chronotypes in epidemiological studies.